Secondary traumatic stress in police officers investigating childhood sexual abuse. Issue 5 (30th April 2018) - Hurrell, Amy-Kate; Draycott, Simon; Andrews, Leanne
Abstract : Purpose: Previous research has indicated that helping professionals working with traumatised individuals are susceptible to adverse effects which can be recognised as secondary traumatic stress (STS). The purpose of this paper is to explore STS in police officer's investigating childhood sexual abuse (CSA) in the UK. Design/methodology/approach: This study employed a cross-sectional, quantitative design. An online questionnaire was completed by 101 Child Abuse Investigation Unit (CAIU) police officers in England and Wales. STS, coping strategies, anxiety, depression and demographic information was collected for all participants. Findings: It was indicated that increased exposure to CSA, measured by number of interviews in the past six months, was associated with higher levels of STS. Positive coping strategies, negative coping strategies, anxiety and depression all had a strong, positive relationship with STS. Research limitations/implications: This paper is a first step to understanding STS in CAIU police officers in the England and Wales. This area of research remains under-developed and would benefit from further attention in the future. Originality/value: This is the first known study of its kind in the UK.